Strength Optimization of Stabilized Peat Using Scrap Tire with Additives - NORAIDA, RAZALI (Universiti Malaysia Sarawak, 2025)
Peat soils are problematic for construction due to high moisture and organic content, low shear strength, and high compressibility. This study examines optimization of stabilized peat strength using Ordinary Portland Cement (OPC), recycled tire materials (rubber crumb (RC) and rubber powder (RP)); and a calcium-based biomass resin stabilizer (SH-85) to identify an optimum additive combination that improves subgrade performance and promotes waste reuse. Peat from Kg. Endap, Kota Samarahan, Sarawak was characterized for physical, index, and mechanical properties; tests comprised Unconfined Compressive Strength (UCS) and California Bearing Ratio (CBR) at 7, 28, and 56 days, supported by Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray Spectroscopy (EDX) for microstructural analysis. Mix designs varied RC/RP at 5%, 10%, and 15% and SH-85 at 3%, 6%, 9%, and 12%, and cement fixed at 5% by dry weight. The optimum formulation of peat + 5% OPC + 15% RC + 6% SH-85 achieved UCS above 345 kPa and CBR exceeding 12%, meeting requirements for subgrades. SEM/EDX indicated a denser, cemented matrix with fewer voids and higher calcium and silicon, consistent with cementitious gel formation and improved bonding. Numerical modelling in GeoStudio (SIGMA/W, SLOPE/W) assessed embankment loading at field scale; a 300 mm stabilized layer reduced settlement to the CREAM threshold of 200 mm and increased the factor of safety to acceptable standards. The Modified Cam Clay model represented compressibility better than Mohr-Coulomb. The findings confirm that combining scrap-tire materials, cement, and SH-85 improves peat strength, stiffness, and stability, supporting resilient infrastructure on problematic soils and linking microstructural enhancements with mechanical performance. Keywords: Peat stabilization, scrap tire rubber, SH-85, cement, UCS, CBR, SEM, EDX, GeoStudio, sustainable geotechnics.